Focal Takotsubo syndrome: clinical features and outcomes - Santoro, Francesco; Arcari, Luca; Núñez Gil, Iván J.; Ragnatela, Ilaria; Di Nunno, Nicola; El-Battrawy, Ibrahim; Guerra, Federico; Novo, Giuseppina; Musumeci, Beatrice; Cacciotti, Luca; Mariano, Enrica; Parisi, Giuseppe; et al. (International journal of cardiology, 2026)
Background - While apical ballooning represents the most common pattern presentation of Takotsubo syndrome (TTS), focal forms have been sporadically reported and lack detailed characterization. Aim of the study is to comprehensively evaluate clinical features and prognostic profile of focal TTS compared to classical phenotypes. - Methods and results - We evaluated 3722 consecutive patients from the GEIST (German-Italian-Spanish Takotsubo) registry (NCT04361994), identifying focal cases based on segmental, non-circumferential wall motion abnormalities and cardiac magnetic resonance data. Clinical, laboratory, and imaging data, with a focus on in-hospital and long-term outcomes were recorded. Focal TTS accounted for 1.2 % of cases (n = 43). Compared to other forms, these patients were younger and exhibited higher LVEF on admission. Emotional triggers were more frequently identified (51 % vs 35 %, p = 0.02), while physical stressors were less common (36 % vs 19 %, p = 0.02). Admission serum levels of NT-proBNP were lower in patients with focal TTS than the control TTS group (1322 ± 643 vs 8699 ± 1553 pg/ml, p < 0.01). Focal dysfunction predominantly affected lateral and anterior segments, and involved rarely inferior and septal segments. Despite patients with focal TTS had fewer in-hospital complications (9 % vs 23 %, p = 0.01), long-term mortality remained comparable across groups (log-rank p = 0.11). - Conclusions - Focal TTS represents a rare and underrecognized entity within the TTS spectrum. Although during hospitalization focal TTS have lower complications, careful long-term surveillance is needed.